Microarray Analysis of Replicate Populations Selected Against a Wing-Shape Correlation in Drosophila melanogaster - Weber, Kenneth E. (Genetics Society of America, 2008)
We selected bidirectionally to change the phenotypic correlation between two wing dimensions in Drosophila melanogaster and measured gene expression differences in late third instar wing disks, using microarrays. We tested an array of 12 selected lines, including 10 from a Massachusetts population (5 divergently selected pairs) and 2 from a California population (1 divergently selected pair). In the Massachusetts replicates, 29 loci showed consistent, significant expression differences in all 5 line-pair comparisons. However, the significant loci in the California lines were almost completely different from these. The disparity between responding genes in different gene pools confirms recent evidence that surprisingly large numbers of loci can affect wing shape. Our results also show that with well-replicated selection lines, of large effective size, the numbers of candidate genes in microarray-based searches can be reduced to realistic levels.